2006
DOI: 10.1177/1076029606293429
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin-1 5A/6A and eNOS T-786C Polymorphisms, MTHFR C677T and A1298C Mutations, and Cigarette-Cannabis Smoking: A Pilot, Hypothesis-Generating Study of Gene-Environment Pathophysiological Associations With Buerger’s Disease

Abstract: Buerger's disease (BD) etiologies are poorly understood. Beyond smoking cessation, medical-surgical treatments have limited success. We hypothesized that mutations associated with arterial vasospasm (stromelysin-1 5A/6A, eNOS T-786C) and C677T-A1298C methylene tetrahydrofolate reductase (MTHFR) interacted with cigarette-cannabis smoking, reducing vasodilatory nitric oxide (NO), promoting arterial spasm-thrombosis. Of 21 smoking BD patients (14 men [2 siblings], 7 women; 20 white, 1 African-American), compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Of note, polymorphism in the promoter region of endothelial NO synthase gene (eNOS‐768C), and subsequent NO expression impairment, have also been detected in TAO patients . Therefore, decreasing the systemic NO levels might promote up‐regulation of endothelial cell adhesion molecules, in particular VCAM‐1 . This might explain the significant difference observed here in VCAM‐1 gene expression between TAO cases and healthy smokers and also between smokers and nonsmokers.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Of note, polymorphism in the promoter region of endothelial NO synthase gene (eNOS‐768C), and subsequent NO expression impairment, have also been detected in TAO patients . Therefore, decreasing the systemic NO levels might promote up‐regulation of endothelial cell adhesion molecules, in particular VCAM‐1 . This might explain the significant difference observed here in VCAM‐1 gene expression between TAO cases and healthy smokers and also between smokers and nonsmokers.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, chronic smoking might also contribute to endothelial cell dysfunction and nitric oxide (NO) bioavailability . NO has an important role in regulating the expression of adhesion molecules on endothelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…We had previously reported that L-arginine treatment improved peripheral circulation in patients with Buerger's disease with peripheral arterial vasospasm who also had the eNOS T-786C mutation [40]. Keeping this in mind we postulated that L-arginine would effectively reduce coronary artery spasm-angina in PVA which has the same eNOS T-786C mutation.…”
Section: Discussionmentioning
confidence: 96%
“…In agreement with literature data, our results of significantly higher levels of TOS, TAC, and their ratios in WBD patients, with respect to smoker healthy controls, suggest that smoking itself is not, per se, the only thing responsible for inducing high oxidative stress and altered antioxidant response. In fact, besides smoking habits, the increased susceptibility to develop WBD might be also due to the presence of a mutation of the T-786C eNOS gene observed in WBD patients, which, through the regulation of nitric oxide bioavailability, may impair the oxidative unbalance caused by cigarette smoke [58]. Accordingly, it has been recently hypothesized that in WBD patients, oxidative stress may originate through the NF-kB/iNOS-NO pathway, able to interact with ROS modifying cells and mitochondria membrane lipids, inducing endothelial dysfunction [51].…”
Section: Discussionmentioning
confidence: 99%